2018
DOI: 10.1089/vbz.2017.2225
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex Polymerase Chain Reaction for Detection of Leishmania Sp. in Sandflies of the Paraná River Islands, Southern Brazil

Abstract: Leishmaniases are classified as tegumentary leishmaniasis (TL) and visceral leishmaniasis (VL). Brazil is among the countries with the highest number of TL and VL cases. This study was undertaken to standardize the multiplex polymerase chain reaction (PCR) for the detection of the genus Leishmania in sandflies of endemic regions, on islands in the Upper Paraná River, northwestern Paraná. The sandflies were collected on 10 islands, from November 2012 to November 2014, with Falcão light traps, identified and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
0
0
Order By: Relevance
“…The lower frequence of CVL vectors in this Palotina study may explain why there are no autochthonous cases of this zoonosis. Other studies, such as those carried out by Santos et al (2016Santos et al ( , 2018 on Paraná River islands, have demonstrated a predominance of L. neivai in this region. This predominance may be related to the capacity of this species to adapt to modified environments and forests as well as forest edges, thus enabling it to invade residences (Reinhold-Castro et al, 2013).…”
Section: Discussionmentioning
confidence: 54%
“…The lower frequence of CVL vectors in this Palotina study may explain why there are no autochthonous cases of this zoonosis. Other studies, such as those carried out by Santos et al (2016Santos et al ( , 2018 on Paraná River islands, have demonstrated a predominance of L. neivai in this region. This predominance may be related to the capacity of this species to adapt to modified environments and forests as well as forest edges, thus enabling it to invade residences (Reinhold-Castro et al, 2013).…”
Section: Discussionmentioning
confidence: 54%